16.0k views
4 votes
Can someone please explain how to do this? Not just the answer, please.

Can someone please explain how to do this? Not just the answer, please.-example-1
User MichaelK
by
5.0k points

1 Answer

5 votes

Answer:

Row n ---> 27th term is 27.

Row T ---> 27th term is 80.

Explanation:

To find the 27th term for the top row, row n, you will use this formula:

an = a1 + f × (n-1)

The first number = 1

The common difference (f) = 1

a27 = 1 + 1 × (27-1)

a27 = 1 + 27 - 1

a27 = 28 - 1

a27 = 27

So, the 27th term is 27.

We will do the same for the row T.

an = a1 + f × (n-1)

The first number = 2

The common difference (f) = 3

a27 = 2 + 3 × (27-1)

a27 = 2 + 81 - 3

a27 = 83 - 3

a27 = 80

So, the 27th term is 80.

User Jacob Tabak
by
5.6k points